Fitness consequences of cousin marriage: a life-history assessment in two populations. (29th November 2023) - Dalzero, Arianna; Ross, Cody T.; Lukas, Dieter
Abstract: Abstract: Cousin marriage, a spousal union between close kin, occurs at high frequencies in many parts of the world. The rates of cousin marriage in humans are concordant with empirical studies that challenge the traditionally held view that reproduction with kin is generally avoided in animals. Similarly, some theoretical models in animal behaviour show that inbreeding avoidance is more constrained than previously thought. Such studies highlight the importance of quantifying the costs and benefits of reproduction among close kin over the whole life-course. Here, we use genealogical data from two human populations with high frequencies of cousin marriage (the Dogon from Mali, and the Ancien Régime nobility from Europe) to estimate these potential costs and benefits. We compare age-specific fertility and survival curves, as well as the projected growth rates, of subpopulations of each marriage type. Fitness costs of cousin marriage are present in terms of reduced child survival (in both populations), while benefits exist as increased fertility for men (in the Dogon) and for women (in the Ancien Régime nobility). We also find some differences in the projected growth rates of lineages as a function of marriage type. Finally, we discuss the trade-offs that might shape marriage decisions in different ecological conditions.